Immunizing adult female mice with a TcpA-A2-CTB chimera provides a high level of protection for their pups in the infant mouse model of cholera. - Gregory A Price; Randall K Holmes (PLoS Neglected Tropical Diseases)
Vibrio cholerae expresses two primary virulence factors, cholera toxin (CT) and the toxin-coregulated pilus (TCP). CT causes profuse watery diarrhea, and TCP (composed of repeating copies of the major pilin TcpA) is required for intestinal colonization by V. cholerae. Antibodies to CT or TcpA can protect against cholera in animal models. We developed a TcpA holotoxin-like chimera (TcpA-A2-CTB) to elicit both anti-TcpA and anti-CTB antibodies and evaluated its immunogenicity and protective efficacy in the infant mouse model of cholera. Adult female CD-1 mice were immunized intraperitoneally three times with the TcpA-A2-CTB chimera and compared with similar groups immunized with a TcpA+CTB mixture, TcpA alone, TcpA with Salmonella typhimurium flagellin subunit FliC as adjuvant, or CTB alone. Blood and fecal samples were analyzed for antigen-specific IgG or IgA, respectively, using quantitative ELISA. Immunized females were mated; their reared offspring were challenged orogastrically with 10 or 20 LD50 of V. cholerae El Tor N16961; and vaccine efficacy was assessed by survival of the challenged pups at 48 hrs. All pups from dams immunized with the TcpA-A2-CTB chimera or the TcpA+CTB mixture survived at both challenge doses. In contrast, no pups from dams immunized with TcpA+FliC or CTB alone survived at the 20 LD50 challenge dose, although the anti-TcpA or anti-CTB antibody level elicited by these immunizations was comparable to the corresponding antibody level achieved by immunization with TcpA-A2-CTB or TcpA+CTB. Taken together, these findings comprise strong preliminary evidence for synergistic action between anti-TcpA and anti-CTB antibodies in protecting mice against cholera. Weight loss analysis showed that only immunization of dams with TcpA-A2-CTB chimera or TcpA+CTB mixture protected their pups against excess weight loss from severe diarrhea. These data support the concept of including both TcpA and CTB as immunogens in development of an effective multivalent subunit vaccine against V. cholerae.